Pets for profit - Lueck, Marianne (Princeton, NJ : Films for the Humanities & Sciences, 2007)
Illustrates trends among American and European consumers that signify dramatic increases in pet-related spending such as animal health insurance, gourmet pet foods, and designer dog clothing. To track the new phenomenon, the film visits the quickly expanding Pets at Home superstore chain, observes the annual'Pet-a-Porter' fashion show at London's Harrods Department Store, and surveys a variety of socioeconomic developments: rising disposable income, a growing number of empty-nest households, and changing attitudes toward the valuation of pets' lives
DVD format
Keywords: Pet industry